EFEKTIVITAS E-GOVERNMENT SIAP PEMKOT PROBOLINGGO DALAM MENINGKATKAN KINERJA PEGAWAI KANTOR KECAMATAN WONOASIH - Veronica Sri Astuti; Andhi Nur Rahmadi; Dinda Sandy (Bajang Institute, 2022)
In an effort to implement the Presidential Instruction regarding the rules for implementing online attendance by employees to the fullest, the Probolinggo City Government made Mayor Regulation No. 18 of 2021 concerning Amendments to Mayor Regulation No. 120 of 2017 concerning the implementation of Civil Servants' Working Days and Hours in the Probolinggo City Government that the implementation of this day and working hours using an electronic attendance list filling system using a finger machine in the form of a fingerPrint/face scan or using SIAP Mobile in the form of a facial scan using an Android-based cellphone. These policy regulations are implemented by various sectoral agencies in the City of Probolinggo. Including the Wonoasih District Office, Probolinggo City. The Probolinggo City Government decided to use an online presence application in an effort to improve employee performance during the COVID-19 pandemic with an application called